2019
DOI: 10.3389/fneur.2019.00618
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of Intracranial and Spinal Cord Cavernous Malformations Predict Aggressive Clinical Presentation

Abstract: Background: Patients with spinal cord cavernous malformations (CMs) are at increased risk for multiple neuraxis CMs. Few studies focused on the natural history of patients with coexistence of intracranial and spinal cord CMs. Methods: Forty patients who underwent both intracranial and spinal MR imaging from a single center were reviewed retrospectively. American Spinal Injury Association (ASIA) impairment scale was used to evaluate neurological and disability status. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Ren Jian (23) reported that patients with cavernous haemangioma (CH) in the spinal canal also have CH of the cranium. However, none of the 35 patients included in the present study had combined CH of the cranium.…”
Section: Discussionmentioning
confidence: 99%
“…Ren Jian (23) reported that patients with cavernous haemangioma (CH) in the spinal canal also have CH of the cranium. However, none of the 35 patients included in the present study had combined CH of the cranium.…”
Section: Discussionmentioning
confidence: 99%
“…1,2,4,9 Spinal cord cavernous malformations (SCCMs) are less common than CCMs and have been considered rare, with relatively less attention in the CCM literature and most reported cases being sporadic nonfamilial SCCMs. [10][11][12][13][14][15][16][17][18][19] A 2009 report on a single Italian family with familial CCM found SCCMs in 5 of 12 patients (41.7%), 2 of which were discovered clinically and 3 of which were discovered with screening MR imaging (3 of 6 screened patients had SCCMs). 20 An additional 2017 report on 13 patients with familial CCM found upper SCCMs in 3 patients (23.1%).…”
mentioning
confidence: 99%
“…10,12 Across 23 literature studies with 825 patients, 671 CMs (81%) were totally resected. 3,7,9,[10][11][12]16,[17][18][19][24][25][26]28,29,32,34,[36][37][38][41][42][43] Transient early postoperative morbidity was reported in 15 out of 116 patients (12%) in 3 series, At the long-term followup 224 patients were improved (27.15%), 393(47.5%) were unchanged, and 72 (8.7%) were worsened, as compared with their preoperative status. These overall results are summarized in Table 2.…”
Section: Discussionmentioning
confidence: 92%